ANALYSIS OF USER SATISFACTION OF DANA APPLICATIONS USING THE END USER COMPUTING SATISFACTION (EUCS) METHOD AND DELONE AND MCLEAN METHOD - Sultan Triabidin, Muchammad; Dwi Nuryana, I Kadek (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
This study aims to analyze the satisfaction of DANA application users. The development of technology today we see a new innovation in the form of digital payments which aims to facilitate non-cash transactions among the public. The model used in this research is End User Computing Satisfaction (EUCS) is a method for measuring the level of user satisfaction by comparing expectations and reality. DeLone and McLean is a model used to identify the factors that cause success. The results showed that the overall level of satisfaction of DANA application users was at a satisfied level. Some variables that can be improved again to have a significant effect are accuracy, easy of use, service quality, system quality, and timeliness. However, some variables that can be improved but do not have a significant effect are content, format, and information quality.